The Effectiveness of Counseling at a Local Crisis Center - Folkesson, Per F. (International Journal of Psychosocial Rehabilitation, 2014)
Samtalsakuten (the Counseling Emergency) is an open crisis center operated in collaboration between the municipalities of Forshaga, Hammarö, Karlstad, and Kil; the Church of Sweden; and the County Council of Värmland. Its mandate is to of- fer crisis counseling to adults who contact the center when they are in an acute life crisis. Samtalsakuten uses a working model influenced by the various traditions and approaches of several talk therapies. The aim of the study was to examine counseling effectiveness at Samtalsakuten. The study was based on a replicated single-case design, and quantitative and qualitative data were collected prior to each counseling session as well as six months after the completion of the session series. Our main finding is that counseling made a significant difference and had a positive effect on anxiety, depression, insomnia, and sense of coherence for clients who completed their sessions in mutual agreement with their therapist